Adoption, Dissemination and Support of the Committee on World Food Security’s Voluntary Guidelines for Food Systems and Nutrition for Use by Governments, Private Sector, Civil Society and Other Stakeholders for Plans, Policies, and Investments - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The Committee on World Food Security (CFS) is the foremost intergovernmental platform for global food security and nutrition. In 2017, CFS began a process to develop Voluntary Guidelines on Food Systems and Nutrition. As a member of CFS, the CGIAR participated in development of these Guidelines, which were approved by member states in February 2021. Governments and other stakeholders use the Guidelines to develop appropriate policies, investments and institutional arrangements to shape food systems to improve nutrition.